Analysis Implementation of Educational Zoning System in Indonesia - Herlina Sakawati; Widyawati Widyawati; Sulmiah Sulmiah; Sirajuddin Saleh (Universitas Negeri Makassar, 2023)
Equality in education has become a polemic that is still being discussed today. Through the zoning system policy, the government seeks to achieve equity and improve the quality of education. This article intends to provide a report on the education zoning system policy in Indonesia which has been implemented since 2017. This study uses the literature review search method using the Open Knowledge Map application as a medium for research and analysis. The research data is in the form of scientific articles obtained from the metadata of scientific journal publications relevant to the study topic. According to the results of the OKM analysis that the author has developed, it is known that as long as the education zoning system policy is implemented various perspectives emerge from the world of education, parents of students, teachers/teaching staff, and stakeholders. This study also found that the education zoning system seeks to realize quality services in terms of service access, service costs, and fairness of education services. The negative impacts and causes of the ineffectiveness of implementing the education zoning system in Indonesia are influenced by other national education policies, school management, and the curriculum they study.